Analysis of overload conditions in distance relay under severe system contingencies - Abu Bakar, A.H.; Yatim, F.M.; Yusof, S.; Othman, M.R. (Elsevier, 2010)
Distance relay protection is widely used worldwide for protection scheme on high voltage transmission lines. This protection tends to be prone to load encroachment condition causing possible undesired tripping condition. Investigations of two system disturbances that occurred in TNB's (Tenaga Nasional Berhad) Grid in the year 2003 and 2005 have clearly revealed the occurrence of load encroachment condition following line overloads after large number of line tripping. Examination of the impedance locus trajectory during the overload events have enabled a distinction be made between power swing and load encroachment phenomena. This paper presents the analysis and findings of the investigation of the load encroachment phenomena of the two events, including other related transmission line contingencies. (C) 2009 Elsevier Ltd. All rights reserved.